Effect of contextual factors of training on training effectiveness study in Kedah State Development Corporation, Kedah Malaysia - Sanjeevkumar, V. Vimala; Kumar M., Dileep; Hu, Yanan (Institute of Management and Information Science, Bhubaneswar, 2012)
Employee training has been a matter of concern and attention by many business fields nowadays. Organizations realize that employee training is an essential element to increase efficiency of job performance and keep their business running, as competitions are getting more intense. Contextualizing this topic to Malaysian industrial scenario so many enterprise implemented various training programs to enhance their employees in skill oriented performance. However, on the contrary, it observed that the training environment still exist shortages in enterprises today. For instance, lack of knowledge of training programs, lack of training need assessment, lack of manpower to plan and design training and development programs, resources, infrastructure, skilled trainers, etc. This study by combining theoretical and empirical research tries to find out the influence of contextual factors on training effectiveness by incorporating variables like work environment, training environment, types of training and personal characteristics of trainees in Kedah State Development Corporation (KSDC) which is the parent company under BDB Company.